A novel multilevel quad-inverter configuration for quasi six-phase open-winding converter - Padmanaban, Sanjeevikumar; Blaabjerg, Frede; Wheeler, Patrick William; Siano, Pierluigi; Martirano, Luigi; Szcześniak, Pawel (2016)
This paper developed a novel quad-inverter configuration for multilevel six-phase asymmetrical open-winding AC converter. Proposal found to be suited for (low-voltage/high-current) applications such as AC tractions and ‘More-Electric Aircraft’ propulsion systems. Modular power circuit comprises of standard four three-phase voltage source inverter (VSI) and each connected to the open-end windings. Each VSIs are incorporated with one bi-directional switching device (MOSFET/IGBT) per phase and two capacitors with neutral point connected. Further, an original modified single carrier five-level modulation (MSCFM) algorithm is developed in this work and easy for implementing in real digital processors. The proposed modulation algorithm is capable of generating, 5-level voltages at each output of four VSI as one equivalent to multilevel inverter. The total power is among the four DC sources and quadruples the capabilities of VSIs. A set of observed results is presented with numerical software analysis (Matlab/PLECS) in balanced working conditions. Always the results shown good agreement in the developed theoretical background.